1998
DOI: 10.1007/s005950050136
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal and scrotal giant liposarcoma: Report of a case

Abstract: The case of a 63 year-old man with a giant scrotal and retroperitoneal tumor is herein reported. The initial symptoms began in the scrotum and subsequent abdominal distention resulted in discomfort 2 years later. The intraabdominal organs were under pressure because of the bulky mass, and the patient had dyspnea. Ultrasonograpy, computed tomography, and fine needle aspiration biopsy investigations all revealed a retroperitoneal tumor suspected to be liposarcoma. At operation, a tumor weighing 42 kg was excised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 10 publications
1
30
0
5
Order By: Relevance
“…Previously, only a few published case reports of inguinal hernia were available, and they discussed an LPS protruding from the retroperitoneum. [4][5][6][7][8][9]12,13 Although 6 is a small number for reliable statistical analysis, we showed that RLPS protruding into the inguinal canal has poor prognosis compared with inguinoscrotal LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, only a few published case reports of inguinal hernia were available, and they discussed an LPS protruding from the retroperitoneum. [4][5][6][7][8][9]12,13 Although 6 is a small number for reliable statistical analysis, we showed that RLPS protruding into the inguinal canal has poor prognosis compared with inguinoscrotal LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports describe RLPS presenting as an inguinal hernia. [4][5][6][7][8][9] Sometimes, a protruding mass in the inguinal region is the only symptom, resulting in a misdiagnosis of ordinary inguinal hernia.…”
mentioning
confidence: 99%
“…This disease may metastasize, and this most frequently affects the lungs and liver. The complementary imaging examinations used are computed tomography, magnetic resonance and angiography, but the diagnosis is made only from the anatomopathology (10,13) .…”
Section: Discussionmentioning
confidence: 99%
“…2 But giant retroperitoneal liposarcomas are very rare malignancy. Till now largest retroperitoneal liposarcoma was reported to be 42kg by Yol S et al 9 Non-specific abdominal pain and discomfort or a palpable abdominal mass with increased abdominal girth is the common presentation accompanying with anorexia, cachexia. The symptoms are often due to compression of adjacent structures (organs) by the enlarged tumour mass.…”
Section: Discussionmentioning
confidence: 99%